(untitled) (Research, Society and Development, 2020)
Introduction: The ectopic pancreas (PE) consists of a congenital malformation, considered rare, defined as the presence of a pancreatic tissue outside its usual topographic location, with a ductal system and independent vascularization. The vast majority of PE cases are asymptomatic, but when the patient is symptomatic, it can manifest itself through bleeding, inflammation, obstruction of adjacent anatomical structures, complications such as pancreatitis and malignant transformations such as adenocarcinoma. Objective: Therefore, the objective of the present study was to carry out a review of cases of pancreatic ectopia and pancreatitis associated with ectopic pancreas, as well as a diagnostic and therapeutic approach when suspected of this disease. Metodology: To this end, an integrative review was developed of studies that address the theme of ectopic pancreas, including a retrospective approach to clinical cases published from 2009 to 2017. The databases consulted for this research were: LILACS (Latin American and Caribbean Literature in Health Sciences), the SciELO library (Scientific Electronic Library on Line) and PubMed (National Center for Biotechnology Information - NCBI, US National Library of Medicine), Google Scholar®. Results and discussion: It is a disease with an approximate incidence of 0.5% -15% in autopsies and 1 in 500 abdominal surgeries. Based on a study with 11,265 patients, 24 (0.21%) abdominal heterotopias were found, of which pancreatic was the most common (0.12%). Conclusion: In this sense, it is concluded that PE is a rare, congenital malformation; most patients have an asymptomatic evolution, however, when present, the symptoms are nonspecific, which makes the diagnosis difficult, being made through radiological exams, endoscopy of the digestive tract or through incidental surgical findings. It is suggested that further studies on the subject are needed for the patient to be diagnosed and treated quickly.